Integrated Geophysical Technique for Characterization of Sedimentary Aquifers of Ankpa, Part of Northern Anambra Basin, Nigeria - Akpah, Fabian A; Musa, Kizito O.; Shuaibu A. M; Akudo, Ernest O; Ahmed II, Jamilu B; Shaibu, Mary M; Nanfa, Andrew C; Jimoh, Jacob B; Oyedokun Tayo, O; Fashipe, Winnies B; Ochogwu Theophilus O (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2025)
This research focused on addressing the need for potable water supply in semi - rural communities through effective groundwater exploration. The study concentrates on the Ankpa Area, within the Northern Anambra Basin in North Central Nigeria. To achieve this, a combined approach utilizing Geomagnetic Very Low-Frequency Electromagnetic (VLF-EM) and Vertical Electrical Sounding (VES) methods were employed. Forty-five (45) locations were subjected to geophysical survey using the DDR3 Terrameter for VES measurements and the ADMT 300 VLF-EM machine. The VES method, employing Schlumberger electrode configuration, was used to investigate variations in subsurface resistivity within depths ranging from 1 to 200 meters. The collected field data underwent meticulous processing and analysis via WinResist software, resulting in a 1D graph that depicts variations in subsurface layer resistivity. The VLF-EM method was applied to map electromagnetic field variations attributable to shifts in geological formations and groundwater presence. By utilizing the ADMT 300 VLF-EM machine, comprehensive data collection across the study area enabled the creation of a 2D subsurface graph. The integration of these two distinct methodologies culminated in a holistic understanding of subsurface structure, significantly enhancing the precision of potential groundwater-bearing zone identification. The outcomes of the study divulged the presence of 5 to 6 geoelectric layers, encompassing topsoil, lateritic soil, clay, sandstone, and shale. These layers exhibited resistivity values spanning from 42.6 Ωm to 100,000.0 Ωm with an average resistivity value of 10352.25Ωm, accompanied by thickness measurements ranging from approximately 0.5 meters to 93.2 meters with an average thickness of 34 meters. The integrated use of VLF-EM and VES methods in the investigation has revealed the potential for groundwater exploration in the study area average to slightly high.